Investigation of Changes in Main Error of Rotary Gas Meters during Their Operation - Fedir Matiko; Oleh Pistun (Energy Engineering and Control Systems)
The main error of rotary gas meters may change during their operation because of mechanical wear of the meter moving parts. Control of changes in metrological characteristics of meters is carried out during periodic metrological verifications. In this paper, an investigation of the change in a main error of rotary gas meters during their operation was carried out based on the results of their metrological verification. The paper considers the results of periodic metrological verifications of rotary gas meters in the laboratories of four gas distribution companies. According to the results of processing the metrological verification protocols, the correlation of the rotary gas meter error with the measured gas volume was confirmed. Based on processing the set of meter error values and the measured gas volume for each of the checked flowrate values, regression dependencies of the error of the meter on the measured gas volume were developed. By averaging the obtained regression dependencies, a generalized dependence of the systematic error of RG-250 rotary gas meter on the measured gas volume was developed. The regression dependencies make it possible to estimate the change in the main error of RG-250 gas meters according to its measured volume and to decide on their additional (out-of-plan) metrological verification. This makes it possible to detect in time gas meters operating with a significant systematic error, and therefore to eliminate this error.